A prospective case-control study on nutritional status and lifestyle risk factors towards quality of life among colorectal cancer and polyp patients in Malaysia - Ashari, Lydiatul Shima (2025)
In Southeast Asian countries, there is a growing incidence and prevalence rate of disease-related malnutrition colorectal cancer (CRC) and its precursor, colorectal polyp, however there are only few reports of this condition. Treatments and the disease itself may affect and impair the overall quality of life (QOL) of CRC survivors. The study aimed to determine the nutritional status and lifestyle risk factors among CRC and polyp patients and their impact on QOL through a prospective case-control study in Malaysia. This study was conducted in two university hospitals in Peninsular Malaysia from June 2020 until December 2022. Patients were recruited through purposive sampling method and a total of 313 patients consisting of 99 and 74 pathologically confirmed CRC and colorectal polyp cases respectively, and 140 controls were included in the analysis. The following information was gathered pre- treatment: Socio-demographic, family and personal medical history, dietary intake, sedentary behaviour, nutritional risk, smoking, clinicopathological, biochemical parameters, and anthropometric profiles. Six months post-treatment, sedentary behaviour, nutritional risk, biochemical parameters, and anthropometric profiles were gathered again, together with treatment and QOL. Multiple logistic regression model revealed that the Kuala Lumpur state (OR=8.89, 95% CI=3.19-24.83; p<0.001), type 2 diabetes mellitus (T2DM) (OR=4.91, 95% CI=1.81-13.29, p=0.002), vitamin/mineral supplements (OR=5.15, CI=2.33-11.39, p<0.001), and saturated fatty acids (SFA) (OR=1.19, 95% CI=1.08-1.31, p<0.001) intake were associated with greater risks of CRC while non-Malay (OR=0.36, 95% CI=0.15-0.87, p=0.024), overweight (OR=0.14, 95% CI=0.04-0.48, p=0.002), increased intake of vitamin D (OR=0.71, 95% CI=0.55-0.92, p=0.008) and dietary fibre (OR=0.81, 95% CI=0.74-0.89, p<0.001) were associated with reduced risk of CRC after the data were adjusted for age and gender. For colorectal polyp, the Kuala Lumpur state (OR=4.36, 95% CI=2.02-9.41, p<0.001) and high cholesterol (OR=1.003, 95% CI=1.001-1.005, p=0.006) intake were associated with increased risk while high thiamin (OR=0.02, 95% CI= 0.00-0.11, p<0.001) and fruits (OR=0.997, 95% CI=0.995-1.000, p=0.035) intake were found associated with decreased of risk. Multiple linear regression model showed that malnourish (β=-18.40, p<0.001) and abdominal obesity (β=-10.07, p=0.020) were negatively associated with QOL after six months of post-treatment. This study advances current understanding of the nutritional and metabolic pathways underlying colorectal cancer and polyp development, providing a foundation for future mechanistic and intervention studies